TERRITORIAL DISTRIBUTION OF THE DEMOGRAPHIC TRANSITION STATE OF MEXICO, 1980-2015 - Hernandez, Jesus Emilio; Juárez, Marcela Virginia Santana; Jaimes, Noel Bonfilio Pineda (Ra’e Ga: o Espaço Geográfico em Análise, 2022)
The purpose of this article is to analyze the territorial distribution of the demographic transition in the State of Mexico, during the period 1980 -2015. The demographic transition for the State of Mexico presents a differentiated evolution over time and territory. The indicators considered are the birth rate and death rate, calculated based on registered births and registered hospital deaths, respectively; as well as the total population for the period 1980-2015. The statistical methods used are the Mean Index Value (MIV) and the bivariate analysis, which gave the guideline to generate the spatial-temporal behavior of the demographic transition and to elaborate the corresponding cartography. Some findings indicate that in the State of Mexico the demographic transition presents four stages: two of them in extensive regions: as the late stage mainly in the west; the full stage in the center and west of the state; the moderate and advanced stages are presented in small regions at random.